Screening for Ischemic Heart Disease with Cardiac CT: Current Recommendations - Matthew J. Budoff (Scientifica)
Cardiovascular disease remains the leading cause of mortality in the US and worldwide, and no widespread screening for this number one killer has been implemented. Traditional risk factor assessment does not fully account for the coronary risk and underestimates the prediction of risk even in patients with established risk factors for atherosclerosis. Coronary artery calcium (CAC) represents calcified atherosclerosis in the coronary arteries. It has been shown to be the strongest predictor of adverse future cardiovascular events and provides incremental information to the traditional risk factors. CAC consistently outperforms traditional risk factors, including models such as Framingham risk to predict future CV events. It has been incorporated into both the European and American guidelines for risk assessment. CAC is the most robust test today to reclassify individuals based on traditional risk factor assessment and provides the opportunity to better strategize the treatments for these subjects (converting patients from intermediate to high or low risk). CAC progression has also been identified as a risk for future cardiovascular events, with markedly increased events occurring in those patients exhibiting increases in calcifications over time. The exact intervals for rescanning is still being evaluated.